External quality assessment of human neutrophil antigen (HNA)‐specific antibody detection and HNA genotyping from 2000 to 2012. Issue 3 (11th May 2013) - Lucas, G.; Porcelijn, L.; Fung, Y. L.; Green, F.; Reil, A.; Hopkins, M.; Schuller, R.; Green, A.; de, M.; Bux, J.
<x xml:space="preserve">Abstract</x> Since 2000, Quality Assurance (QA) exercises for the detection and identification of granulocyte antibodies and DNA typing for human neutrophil antigens (HNA) have been distributed within the International Granulocyte Immunobiology Workshops, which are linked to International Society of Blood Transfusion. The exercises were standardised at the outset to enable laboratory performance to be monitored. Between 2000 and 2012, nine exercises were distributed to 20 laboratories. Overall, 45 examples of 42 unique samples containing defined granulocyte reactive antibodies were distributed for serological analysis together with 20 samples for HNA genotyping. The level of satisfactory serological performance was initially set at 50% and later increased to 70%, while the 'cut‐off' for HNA genotyping was set at 100% after 2008. Failure to achieve the minimum score in the QA exercises in consecutive years resulted in temporary exclusion. In 2000, the 15 participating laboratories had a mean score of 56.1% for serological analysis and 13 laboratories attempted HNA‐1a and ‐1b genotyping, while 11 attempted HNA‐1c typing. Steady improvements in proficiency for serological testing and HNA typing occurred in subsequent exercises. In 2012, the mean score for serology was 88.5% and 12/13 laboratories scored 100% for HNA‐1a, ‐1b, ‐1c, ‐3a, ‐3b, ‐4a, ‐4bw, ‐5a and ‐5bw genotyping. These QA exercises have provided an invaluable tool to monitor and improve the standard of granulocyte immunology investigations for participating laboratories, thereby enhancing performance for both clinical investigations and donor screening programmes to reduce the incidence of TRALI.